A Design Thinking Approach in Developing Value Proposition to Enhance Virtual Debit Card User Experience - Mufadlol, Abdurrohman Ibnul; Pawekas, Dewo Suryo (Journal of Social Work and Science Education, 2025)
In the increasingly competitive digital payment industry, a deep understanding of user needs is key to creating a superior value proposition. This study applies a Design Thinking approach to develop and deliver a value proposition on Komcards virtual debit card, with the primary goal of improving user experience. Through a series of stages of empathy, problem definition, ideation, prototyping, and testing, this study aims to identify key aspects that influence user perception, such as ease of use, content comprehension, and perceived security. The results of the study found that the Design Thinking approach effectively improved the quality of user interaction with the service. However, despite the increase in positive perceptions, user interest in authorization services has not changed significantly, indicating a gap in creating loyalty. This study provides recommendations on the importance of continuous education strategies, optimization of navigation features, and implementation of systems provided as drivers of user innovation. The results of this study can also be used as a framework that can be applied by financial service providers in designing more relevant and sustainable innovations so that future digital product development continues to involve iterations based on user input to ensure a match between market needs and solutions.